Myocardial Infarction and Aortic Root Mycotic Aneurysm Complicating Aortic Valve Endocarditis: Utility of Cardiac CT - Aimee E. Moores; Michael S. Cahill; Todd C. Villines (Case Reports in Medicine)
Aortic mycotic aneurysms are a rare but life-threatening potential complication of infective endocarditis. Rapid deterioration of the vascular wall in highly focal areas makes these pseudoaneurysms particularly prone to rupture, resulting in uncontrolled aortic hemorrhage. While computed tomography angiography (CTA) is the imaging modality of choice for the evaluation of mycotic aneurysms, it is not routinely performed in patients with known or suspected infective endocarditis (IE). However, current valvular heart disease guidelines support the use of cardiac CTA in cases of IE and suspected perivalvular extension when there is inadequate or ambiguous visualization on echocardiography. Here, we describe a case of IE in which cardiac CTA was used for two purposes: to assess perivalvular complications and to define coronary anatomy in a patient with a suspected embolic myocardial infarction. Subsequent detection of an aortic root mycotic aneurysm not previously demonstrated on transthoracic or transesophageal echocardiography allowed for timely and uncomplicated surgical intervention, while avoiding invasive coronary angiography.